Occurrence, Distribution, and Genetic Diversity of Alfalfa (Medicago sativa L.) Viruses in Four Major Alfalfa-Producing Provinces of China - Guo, Zhipeng; Zhang, Tingting; Chen, Zhao; Niu, Junpeng; Cui, Xuewen; Mao, Yue; Hassan, Mahmood Ul; Kareem, Hafiz Abdul; Xu, Nan; Sui, Xin; Gao, Shuanghong; Roy, Momi; et al. (Frontiers in Microbiology, 2022)
Alfalfa (Medicago sativa L.) is one of the most widely cultivated forage crops in the world. China is the second largest producer of alfalfa in terms of the planting area worldwide, with Gansu, Henan, Inner Mongolia, and Shaanxi provinces being the production hubs. Alfalfa viruses have been reported on a small-scale survey in some of these areas, but they have not been well characterized. In the present study, seven viruses were detected in 12 fields of 10 cities/counties of the four abovementioned provinces by high-throughput sequencing and assembly of small RNA. Their incidence, distribution, and genetic diversity were analyzed by enzyme-linked immunosorbent assay, polymerase chain reaction (PCR)/reverse transcription-PCR and clone sequencing. The results showed that alfalfa mosaic virus (AMV), pea streak virus (PeSV), lucerne transient streak virus (LTSV), alfalfa dwarf virus (ADV), Medicago sativa alphapartitivirus 1 (MsAPV1), MsAPV2, and alfalfa leaf curl virus (ALCV) were the main viruses infecting alfalfa in four examined provinces. AMV and MsAPV1 had the highest incidences in all 4 provinces. SDT analysis of the 7 viruses isolated in China revealed a highly conserved among AMV, LTSV, ADV, MsAPV1, MsAPV2, and ALCV, but the sequence was a high variation between China isolates to abroad isolates in PeSV, ADV, and ALCV. To our knowledge, this is the first report of ADV in Inner Mongolia and Gansu, ALCV in Inner Mongolia, MsAPV1 and MsAPV2 in all 4 provinces, and PeSV and LTSV in China. These findings provide a basis for future research on the genetic evolution of alfalfa viruses in China and on strategies to prevent diseases in alfalfa caused by these viruses.